An overview of climate change adaptation and mitigation research in Africa - Baninla, Yvette; Sharifi, Ayyoob; Allam, Zaheer; Tume, Suiven John Paul; Gangtar, Ngeh Najibullah; George, Ngiamte (Frontiers in Climate, 2022)
Research on climate change has increased significantly since the 1970s. There has also been a particular focus on Africa, given its vulnerability to climate change impacts and its urbanization trends that may have massive implications for climate change adaptation and mitigation. Despite the wealth of publications on climate change in Africa, there is a lack of review studies that highlight the overall research landscape. If this status of climate research is clarified, African countries can better deal with climate change. Hence, this paper aims to improve our understanding of the status and trends of research on climate change adaptation and mitigation in Africa. Our review, straddling from 1990 to late 2021, recognizes the foundations that underpin climate change adaptation and mitigation literature. Based on keywords associated with Africa’s climate change adaptation and mitigation, we undertook bibliometric research by collecting 3,316 related SCI/SSCI articles. In addition, we provided a thematic evolution over three decades, compartmentalized into four sub-periods (1990–2007; 2008-2014; 2015-2019; 2020-2021). Priority research topics and themes have been dynamic over time, with some core concepts receiving more attention (vulnerability, food, water, and energy security). Although the number of published articles exhibited a rapidly growing trend, their distribution is extremely uneven. Articles were mainly published by institutions from certain parts of the continent, with the University of Cape Town, making the highest contribution. About 72% of the existing studies focused on climate change adaptation, while climate change mitigation was less represented with 22%. The results also showed that researchers have examined not all African countries. South Africa, Ethiopia, and Ghana are hot spots, while most countries are largely neglected. Africa and African countries need to improve their future research ability on climate change mitigation. Assessing climate change risks and measures in African countries should be prioritized.